Irony and the Social Construction of Contradiction in the Humor of a Management Team - Hatch, Mary Jo (Organization Science, 1997)
The thesis I explore in this essay is that organizational members use humorous remarks to discursively construct and organize their cognitive and emotional experiences in and of their organizations. My assumptions are that: (1) organizations are socially constructed through discourse about them (especially managerial discourse), (2) humorous discourse provides a contradiction-centered construction of organizations that operates in the domains of both cognition and emotion, and (3) interpretation of the text of ironic remarks will suggest the processes by which contradictions and their cultural and emotional contexts are socially constructed through discourse. In this essay I use a form of analysis that I developed in relation to humor theory (Mulkay [Mulkay, M. 1988. On Humor. Basil Blackwell, Oxford, UK.]), theories of irony (Brown [Brown, R. H. 1977. A Poetic for Sociology: Toward a Logic of Discovery for the Human Sciences. University of Chicago Press, Chicago, IL.], Weick and Browning [Weick, K. E., L. D. Browning. 1986. Argument and narration in organizational communication. J. G. Hunt, J. D. Blair, eds. 1986 Yearly Review of Management of the Journal of Management 12 243–259) and Rorty's (Rorty, R. 1989. Contingency, Irony, and Solidarity. Cambridge University Press, Cambridge, UK.) concept of the ironic disposition to interpret spontaneous humorous exchanges observed during the regular meetings of a group of middle managers. My interpretations of ironically humorous remarks indicate that the managers in my study constructed at least some of their cognitive and emotional experiences in contradictory ways including: possible/impossible, great/horrible, comic/serious, and up-to-date/unprepared. The interpretations also suggest how, in constructing contradiction, the managers reflexively constructed themselves in relation to their organization. The analysis points to a paradoxical understanding of organizational stability and change and informs a contradiction-centered view of organizations.